Modul Intervensi Keperawatan untuk Mencegah Infeksi Luka Operasi pada Pasien Bedah di Wilayah RSUD Labuang Baji Makassar - Ismail Ismail; Mawwal Ulfiah.J; Sukriyadi Adi; Ade Nurkhotimah; Sri Wahyuni Mansur (Jurnal Inovasi Pengabdian Masyarakat Celebes, 2025)
Background: Surgical site infection (SSI) is a common postoperative complication that increases hospitalization and morbidity rates. Nurses are essential in preventing SSI through evidence-based intervention. Objective: This research aims to develop evidence-based nursing intervention modules to prevent surgical wound infection in surgical patients, as well as examine the need and effectiveness of the module in improving the knowledge and skills of nurses. Methods: It utilized a Research and Development (R&D) approach with Borg & Gall model including needs analysis, design, validation, limited trials, evaluation, and implementation. It was conducted at Labuang Baji Hospital Makassar VIP room involving seven nurses as respondents. Observation, interviews, and questionnaires were used. Results: It showed nursing intervention module improved nurses' knowledge and skills in preventing surgical wound infections and strengthening nurses’ education. The module was considered understandable, relevant, and applicable. The obstacles were high workload and less training. Conclusions: This module is effective as an educational medium which can be implemented systematically in clinical practice to reduce surgical wound infections incidence.